MR of the head and neck: comparison of fast spin-echo and conventional spin-echo sequences. - Fulbright, R; Panush, D; Sze, G; Smith, R C; Constable, R T (American Journal of Neuroradiology, 1994)
PURPOSE To compare conspicuousness of head and neck lesions on fast spin-echo sequences and conventional spin-echo sequences. METHODS Forty consecutive patients with 61 head and neck lesions were evaluated. Lesion conspicuousness was qualitatively compared on conventional spin-echo and fast spin-echo sequences, using both spin-density and T2-weighted images. Thirty-six lesions had surgical or pathologic confirmation, and 25 were assigned a presumptive diagnosis based on clinical evaluation and imaging findings seen on conventional spin-echo T1- and T2-weighted sequences. Forty lesions were related to neoplasms; 21 lesions consisted of infectious, vascular, or inflammatory abnormalities. RESULTS Fast spin-echo sequences provided improved lesion conspicuousness in 91% of spin-density images, in 77% of T2-weighted images, and in 84% of the combined spin-density and T2-weighted images. CONCLUSION By providing shorter imaging times and equal or superior lesion conspicuousness, long-repetition-time fast spin-echo sequences can replace long-repetition-time conventional spin-echo sequences in evaluation of the head and neck.